2016
DOI: 10.13005/bbra/2043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-Care Education with Telephone Follow-up on Self-Efficacy level in Hemodialysis Patients

Abstract: Introduction: Patients under hemodialysis treatment face various physical and mental problems. One of the basic principals in prevention of complications in these patients is education. But education, solely, does not result in improve hemodialysis control situation, therefore, more attention should be paid to follow-up. Currently, by coming new communications systems and telemedicine, using them, such as follow-up methods, is inevitable. This study aimed to determine the effect of self-care education with tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 5 publications
1
22
0
1
Order By: Relevance
“…This increases patients' knowledge about their diseases and diagnosis, the advantages and disadvantages of different treatments and helps infertile individuals make informed decisions about treatment methods (Krol, Sanderman, & Suurmeijer, 2003). Nurses can improve patients' quality of life via nursing processes: they should make careful evaluations of patients' quality of life and regulate their care models accordingly (Kargar Jahromi, Poorgholami, Rahmanian, & Rahmanian, 2016;Alligood, 2004). Evaluation of quality of life of infertile couples helps healthcare providers and special-care nurses choose the right treatment and support care (Omranifard, Afshar, Mehrabi & Asadollahi, 2007;Yaghmaee, Mohammadi & Alavi Majd, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This increases patients' knowledge about their diseases and diagnosis, the advantages and disadvantages of different treatments and helps infertile individuals make informed decisions about treatment methods (Krol, Sanderman, & Suurmeijer, 2003). Nurses can improve patients' quality of life via nursing processes: they should make careful evaluations of patients' quality of life and regulate their care models accordingly (Kargar Jahromi, Poorgholami, Rahmanian, & Rahmanian, 2016;Alligood, 2004). Evaluation of quality of life of infertile couples helps healthcare providers and special-care nurses choose the right treatment and support care (Omranifard, Afshar, Mehrabi & Asadollahi, 2007;Yaghmaee, Mohammadi & Alavi Majd, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Torrens et al report similar findings. Evidently, MMT can not only reduce or eliminate one's dependence on drugs, but improves psychological health and lowers the rate of social crimes 21,22 . On the other hand, administration of buprenorphine is a much less popular treatment in Iranian clinics: currently, out of the 500,000 drug addicts who are undergoing maintenance therapy in Iran, 430,000 (87%) are on methadone and 65,000 (13%) are on buprenorphine 15 .…”
Section: Discussionmentioning
confidence: 99%
“…If a patient with withdrawal symptoms and a serious concurrent disease desires a long-term recovery program, maintenance therapy with legal agonists should be suggested to him or her immediately. The fact that maintenance therapy with legal agonists is more effective than detoxification methods in reducing the rates of side effects and deaths has been proven beyond doubt 17,20,22 . Comparing the effectiveness of two detoxification methods for opium-dependent patients, Taraghi et al (2005) discovered that methadone and buprenorphine acted similarly in controlling the patients' withdrawal symptoms; yet, the patients were more willing to use methadone because of its lower cost.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that telephone follow-up and tele-education by nurses lead to heightened self-care in patients (27,28). Telenursing denotes the provision of nursing services through the use of information technologies.…”
Section: Introductionmentioning
confidence: 99%